2019
DOI: 10.1098/rsos.190069
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and discrimination among closely versus distantly related species of Drosophila

Abstract: Fighting between different species is widespread in the animal kingdom, yet this phenomenon has been relatively understudied in the field of aggression research. Particularly lacking are studies that test the effect of genetic distance, or relatedness, on aggressive behaviour between species. Here we characterized male–male aggression within and between species of fruit flies across the Drosophila phylogeny. We show that male Drosophila discriminate between consp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In contrast, Gupta et al. ( 2019 ) found that aggressive behavior tended to be lower toward heterospecifics than toward conspecifics, which would if anything tend to promote coexistence rather than spatial segregation of the two species.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, Gupta et al. ( 2019 ) found that aggressive behavior tended to be lower toward heterospecifics than toward conspecifics, which would if anything tend to promote coexistence rather than spatial segregation of the two species.…”
Section: Discussionmentioning
confidence: 86%
“…The 2017, 2018, and 2019 datasets included cages populated with both D. americana and D. novamexicana , while the 2020 datasets featured only one type of fly per cage. Several species of male Drosophila have indeed been shown to demonstrate differential patterns of aggression toward conspecific versus heterospecific males (Gupta et al., 2019 ). However, this finding was primarily observed when the species involved were distantly related, whereas D. americana and D. novamexicana are sister species thought to have diverged less than 0.5 MYA (Caletka & McAllister, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, since we independently assigned behaviors to categories, prior meta-analyses and individual studies may have conflated multiple different behaviors under the aggression label. For example, aggression is sometimes defined as agonistic interactions with conspecifics (Oyegbile and Marler, 2005), heterospecifics (Vullioud et al, 2013), or humans (Class et al, 2014), and these behaviors are not necessarily be equivalent (Gupta et al, 2019; Peiman and Robinson, 2010).…”
Section: Discussionmentioning
confidence: 99%